Pattern and Pain Assessment of Musculoskeletal Disorders Attending to Physiotherapy Services in Selected Physiotherapy Centres of Dhaka City (Delta Medical College Journal, 2015)
Background: Musculoskeletal disorders are the most common causes of severe long-term pain and physical disability, affecting hundreds of millions of people around the world. Among different modalities of treatment and management for musculoskeletal pain, physiotherapy might be cost-effective.Objective: The aim of the study was to determine the pattern and pain assessment of musculoskeletal disorders attending to physiotherapy services in selected physiotherapy centers of Dhaka city.Materials and method: It was a cross sectional study. Sample size was 400 and a pre-tested, modified, semi-structured questionnaire was used to collect the data. Data were analyzed using SPSS software version 16.0.Results: Majority of the respondents (69.2%) belonged to 46-65 year age group with least in extreme age groups. Mean±SD of age was 33.58±12.33 years. Most of the respondents were male (69.2%). Study revealed that neck pain (75.2%) was the major complaint followed by back pain (48.00%). Regarding pattern of pain, intermittent (73.2%) type was predominant. Muscle spasm (29.2%) was the main cause for musculoskeletal pain followed by degenerative diseases (27.5%). Of the respondents 55.00% received traction, 91.25% exercise, 21.25% manipulation, 97.95% short wave diathermy, 85.00% ultrasound therapy, 33.75% infra red ray, and 12.75% electrical stimulation as physiotherapy treatment. There were statistically significant difference between sex and severity of pain (p=0.019), educational status and pain persisting time in years (p=0.000). There was also statistically highly significant difference between severity of pain responses before and after physiotherapy treatment (p=0.000).Conclusion: Study concluded that common areas of musculoskeletal pain were neck followed by back and shoulder and pain characteristics were intermittent, radiating, numbness, burning in nature. Respondents had taken medication and different type of physiotherapy services, including traction, exercise, short wave diathermy and ultrasound therapyDelta Med Col J. Jul 2015; 3(2): 83-88